1998
DOI: 10.1088/0256-307x/15/7/023
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Electric and Structural Properties of Ti 1-x Al x N Thin Films

Abstract: A sequence of Til-,Al,N films has been prepared by rf reactive magnetron sputtering. The optical and electric properties versus aluminum content x have been studied. Values suitable for magneto-optic protective layers have been achieved in Til-,Al,N thin films with aluminum content x > 0.75. X-ray diffraction results show that Til-,Al,N thin films in this study are a bcc structure u p to x = 0.75, further increase in the aluminum content gives a wurtzite structure. All of the results show that the optical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Alternatively to charm enhancement, the number of muon pairs entering the phase space window of the experiment could be increased, while the total charm production cross section remains unchanged. This could result from, e.g., the smearing of the D/D pair correlation resulting from rescattering of the charmed quarks or mesons in the surrounding dense matter [9]. It was also suggested that the mass spectrum of the Drell-Yan dimuons could be modified in heavy-ion collisions with respect to the proton-nucleus case, because of higher-twist effects that increase the yield of low mass dimuons [10].…”
Section: Muon Spectrometermentioning
confidence: 99%
“…Alternatively to charm enhancement, the number of muon pairs entering the phase space window of the experiment could be increased, while the total charm production cross section remains unchanged. This could result from, e.g., the smearing of the D/D pair correlation resulting from rescattering of the charmed quarks or mesons in the surrounding dense matter [9]. It was also suggested that the mass spectrum of the Drell-Yan dimuons could be modified in heavy-ion collisions with respect to the proton-nucleus case, because of higher-twist effects that increase the yield of low mass dimuons [10].…”
Section: Muon Spectrometermentioning
confidence: 99%
“…Theoretical models have been devised to understand this dimuon excess. Those include rescattering of the open charm mesons with the surrounding hadronic constituents [9]. This approach can not however reproduce the dimuon mass and transverse momentum spectra for central nuclear collisions [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, such an increase is not easily justified theoretically [7], and would also be difficult to reconcile with the current understanding of the observed J/Ψ suppression. Another possibility has been pursued by Lin and Wang [8] who showed that D-meson rescattering in hot/dense matter (without invoking anomalous enhancement) might generate a transverse momentum broadening which can enrich the µ + µ − phase space covered by the NA50 experiment. The resulting increase is, however, much too small to explain the data [3].…”
Section: Introductionmentioning
confidence: 99%